Influence of plant traits, soil microbial properties, and abiotic parameters on nitrogen turnover of grassland ecosystems. Issue 11 (21st November 2016) - Legay, Nicolas; Lavorel, Sandra; Baxendale, Catherine; Krainer, Ute; Bahn, Michael; Binet, Marie‐Noëlle; Cantarel, Amélie A. M.; Colace, Marie‐Pascale; Foulquier, Arnaud; Kastl, Eva‐Maria; Grigulis, Karl; Mouhamadou, Bello; et al.
Abstract: Although it is known that multiple interactions among plant functional traits, microbial properties, and abiotic soil parameters influence the nutrient turnover, the relative contribution of each of these groups of variables is poorly understood. We manipulated grassland plant functional composition and soil nitrogen (N) availability in a multisite mesocosm experiment to quantify their relative effects on soil N turnover. Overall, root traits, arbuscular mycorrhizal colonization, denitrification potential, as well as N availability and water availability, best explained the variation in measured ecosystem properties, especially the trade‐off between nutrient sequestration and plant biomass production. Their relative contributions varied with soil N availability. In relatively N‐poor soils (10–20 μg·N·g −1 soil), N turnover was mainly controlled by microbial properties and abiotic soil parameters, whereas in the relatively N‐rich soils (110–120 μg·N·g −1 soil), N turnover was mainly controlled by plant traits and microbial properties. This experiment is a strong demonstration of the importance of functional characteristics of both plants and soil microbes, and their interplay with soil N availability, for N turnover in grassland soils.